Water metabolism in post-op Cesarean - Keymer F., Eduardo (2015)
From the point of view of water metabolism, normal delivery is not a factor of stress and yes it is caesarean section. Surgical injury produced by caesarean section is greater than that caused by surgery of middle severity. In the post-operative caesarean overhydration which is greater in the extracellular to the intracellular it occurs. The action of the stress produced by cesarean section ceases around the fourth day of the post-operative period, which translates into greater diuresis and water outlet intra-to extracellular.